1984
DOI: 10.1007/bf01887796
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the diagnosis of acute hemorrhagic-necrotizing pancreatitis using contrast-enhanced CT

Abstract: Twenty-eight consecutive patients with a first attack of alcohol-induced pancreatitis were studied using contrast-enhanced CT. The findings on CT were then related to the course of the disease. The patients with acute hemorrhagic-necrotizing pancreatitis showed significantly lower enhancement values of the pancreatic parenchyma than those with milder forms of the disease. The next 20 patients with severe pancreatitis were scanned using a slightly modified procedure. The enhancement values were calculated and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…Several authors have reported on groups with a majority of severe cases [5,12,14,15,21], This study is based on a patient material exhibiting the total spectrum of pancreatitis with the majority being nonsevere cases and only 17% having clinically severe pancreati tis. A diagnostic sensitivity of 83% and a specificity of 80% in this study indicate that the method is useful for clinical purposes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have reported on groups with a majority of severe cases [5,12,14,15,21], This study is based on a patient material exhibiting the total spectrum of pancreatitis with the majority being nonsevere cases and only 17% having clinically severe pancreati tis. A diagnostic sensitivity of 83% and a specificity of 80% in this study indicate that the method is useful for clinical purposes.…”
Section: Discussionmentioning
confidence: 99%
“…At contrast injection a reduced uptake corre sponding to less than 20 HU was considered as a sign of pancreatic ischaemia, based on results from Kivisaari et al [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequential scanning of a selected level of the pancreas is then performed. The contrast enhancement of the pancreas is recorded and plotted on a standard curve [9]. The results have shown that in all patients with severe hemorrhagic necrotizing pancreatitis, the contrast en hancement is decreased significantly as com pared to those patients with milder forms of the disease [28].…”
Section: Computed Tomographymentioning
confidence: 99%
“…[39][40][41][42]. The main differences in estimating the severity of AP rely on the degree of contrastenhancement of the pancreatic parenchyma [40]. the quantification of pancreatic necrosis in percent ol the entire gland [39].…”
Section: Prognosis Via C T Scanmentioning
confidence: 99%